Raman Study of Pathogenic Candida auris: Imaging Metabolic Machineries in Reaction to Antifungal Drugs - Pezzotti, Giuseppe; Kobara, Miyuki; Nakaya, Tamaki; Imamura, Hayata; Asai, Tenma; Miyamoto, Nao; Adachi, Tetsuya; Yamamoto, Toshiro; Kanamura, Narisato; Ohgitani, Eriko; Marin, Elia; Zhu, Wenliang; et al. (Frontiers in Microbiology, 2022)
The multidrug-resistant Candida auris often defies treatments and presently represents a worldwide public health threat. Currently, the ergosterol-targeting Amphotericin B (AmB) and the DNA/RNA-synthesis inhibitor 5-flucytosine (5-FC) are the two main drugs available for first-line defense against life-threatening Candida auris infections. However, important aspects of their mechanisms of action require further clarification, especially regarding metabolic reactions of yeast cells. Here, we applied Raman spectroscopy empowered with specifically tailored machine-learning algorithms to monitor and to image in situ the susceptibility of two Candida auris clades to different antifungal drugs (LSEM 0643 or JCM15448T, belonging to the East Asian Clade II; and, LSEM 3673 belonging to the South African Clade III). Raman characterizations provided new details on the mechanisms of action against Candida auris Clades II and III, while also unfolding differences in their metabolic reactions to different drugs. AmB treatment induced biofilm formation in both clades, but the formed biofilms showed different structures: a dense and continuous biofilm structure in Clade II, and an extra-cellular matrix with a “fluffy” and discontinuous structure in Clade III. Treatment with 5-FC caused no biofilm formation but yeast-to-hyphal or pseudo-hyphal morphogenesis in both clades. Clade III showed a superior capacity in reducing membrane permeability to the drug through chemically tailoring chitin structure with a high degree of acetylation and fatty acids networks with significantly elongated chains. This study shows the suitability of the in situ Raman method in characterizing susceptibility and stress response of different C. auris clades to antifungal drugs, thus opening a path to identifying novel clinical solutions counteracting the spread of these alarming pathogens.